2012
DOI: 10.2460/ajvr.73.5.664
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral administration of firocoxib for the management of musculoskeletal pain and lameness associated with osteoarthritis in horses

Abstract: Firocoxib significantly improved lameness scores throughout the 14-day period with few adverse effects. Firocoxib can be a safe cyclooxygenase-2-specific NSAID for the treatment of musculoskeletal pain and lameness associated with osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 13 publications
0
38
0
3
Order By: Relevance
“…As such, the dose of 0.5 mg/kg used in our study was based on pharmacokinetic information available in the horse labeled for use at 0.1 mg/kg. The equineapproved dose demonstrated analgesia in naturally occurring lameness following multiple daily doses (Orsini et al, 2012). More recently, it has been suggested to use a loading dose in horses to achieve steady state drug concentrations more quickly (Cox et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the dose of 0.5 mg/kg used in our study was based on pharmacokinetic information available in the horse labeled for use at 0.1 mg/kg. The equineapproved dose demonstrated analgesia in naturally occurring lameness following multiple daily doses (Orsini et al, 2012). More recently, it has been suggested to use a loading dose in horses to achieve steady state drug concentrations more quickly (Cox et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Firocoxib was administered at 0.1 mg/kg once daily, a common dose in equine practice and according to package label directions. This dosing regimen was chosen to mimic the most frequent clinical use of this drug in our practice setting and for its efficacy to treat pain associated with osteoarthritis . Some publications, however, have reported that firocoxib concentrations reach a steady‐state sooner after administration of a loading dose because it may take up to 7 days to achieve steady‐state concentration with a once daily 0.1‐mg/kg dose.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that firocoxib was a safe treatment for musculoskeletal pain and lameness in horses with OA, with only four of 467 horses (0.9%) having adverse effects, which included edema of lips and gums, mild episodes of colic, and mild oral ulcers. 53 Without a control group in this study, there was likely a very high bias for veterinarians and owners to identify the horses as improved because they knew the horse was receiving a treatment, which is comparable to the control horses improving on clinical evaluations in the first study identified. This is an indication that more controlled studies with objective measures are needed to truly assess firocoxib's effect on lameness.…”
Section: Effect Of Firocoxib On Oamentioning
confidence: 94%